Deictic pronouns in the Egypt-Amarna letters - Westhuizen, J. P. van der (Journal for semitics, 2010)
The aim of this paper is to investigate, verify and present the deictic pronouns, with their functions and their application, as they appear in the Egypt-Amarna letters. This involves EA 1, 5, 31, 99, 162, 367, 369 and 370; 163 and 190 are too fragmentary for consideration while 31 is in Hittite. The deictic pronouns are divided into four categories of pronouns with a common denominator, namely the function of pointing to, or indicating, a specific component in the discourse context. The four categories are the reflexive pronoun, the demonstrative pronouns, the anaphorics and the determinative pronoun. Being short of a real reflexive pronoun, the noun ramânu (''self'') is employed in conjunction with the appropriate personal pronoun. However, for whatever reason, the scribes of the Egypt letters did not use ramânu; instead they used a circumscribing phrase of verb plus independent personal pronoun. With reference to the demonstrative pronouns, attention will be given to their morphological and morphosyntactic aspects. With the anaphorics the nominative and the accusative cases will also receive the required attention and with the determinative pronoun consideration will be given to genitive constructions, relative clauses and determined clauses, that is, subject clauses and object clauses.